Differential Regulation of GPCRs—Are GRK Expression Levels the Key? - Matthees, Edda S. F.; Haider, Raphael S.; Hoffmann, Carsten; Drube, Julia (Frontiers in Cell and Developmental Biology, 2021)
G protein-coupled receptors (GPCRs) comprise the largest family of transmembrane receptors and their signal transduction is tightly regulated by GPCR kinases (GRKs) and β-arrestins. In this review, we discuss novel aspects of the regulatory GRK/β-arrestin system. Therefore, we briefly revise the origin of the “barcode” hypothesis for GPCR/β-arrestin interactions, which states that β-arrestins recognize different receptor phosphorylation states to induce specific functions. We emphasize two important parameters which may influence resulting GPCR phosphorylation patterns: A) direct GPCR–GRK interactions and B) tissue-specific expression and availability of GRKs and β-arrestins. In most studies that focus on the molecular mechanisms of GPCR regulation, these expression profiles are underappreciated. Hence we analyzed expression data for GRKs and β-arrestins in 61 tissues annotated in the human protein atlas. We present our analysis in the context of pathophysiological dysregulation of the GPCR/GRK/β-arrestin system. This tissue-specific point of view might be the key to unraveling the individual impact of different GRK isoforms on GPCR regulation.